Information technology as an entrance to the adoption of electronic management : a socio-organizational reading - Allouti, Achour; Moussa, Abdennour (Journal of Human Sciences, 2022)
Through this paper, we seek to present a visionary organizational vision in order to achieve effective electronic management based on the conceptual connotations of information technology and electronic management, with reference to the physical and organizational aspects as the main tributaries to activate the format of information technology, in addition to the human resource as a support and the focus of the construction process, Performing administrative functions in the light of information technology, which contributes to the improvement of public service in Algerian institutions, in line with the requirements of changes in the external environment in the forefront of information technology.